Analysis of Non-Formal Education Policy for Life Skills - Syafruddin (Open Access Indonesia Journal of Social Sciences, 2022)
Non-formal education can help graduates formal education. This is related to the real need for labor. In fact, everyone needs a job after graduation in order for them to survive. So, they must have the knowledge and skills to enter real jobs. In addition, formal education also requires non-formal education through courses and practicing their abilities. The government must improve life skills with specifications that are in accordance with needs. In this context, life skills education programs are education capable of imparting practical skills used in relation to job market needs, opportunities, or industry in our industrial community. The main purpose of life skills education is to prepare students to be able and have the skills to maintain their survival and develop their abilities in the future. In essence, life skills education is an increase the relationship between education and real-life values.